Identification of human heat shock protein 60 (Hsp60) and anti-Hsp60 antibodies in the peripheral circulation of normal individuals - Graham Pockley, A. (Cell Stress Society International, 1999)
Although primarily regarded as being intracellular, this study has identified the presence of heat shock protein 60 (Hsp60) in the peripheral circulation of normal individuals. The median Hsp60 concentration was approximately 3.5-fold higher in females than in males and significantly higher levels of anti-human Hsp60 antibodies were also detected in females. There were no differences in the levels of antibodies to mycobacterial Hsp60 between males and females, nor did antibody levels correlate with Hsp60 concentrations. Hsp60 was not released from mitogenically stimulated peripheral blood mononuclear cells. The potential physiological roles for circulating Hsp60 are unknown. Given the emerging evidence that inappropriate reactivity to heat shock proteins is involved in autoimmune disease and that T cells responsive to self Hsp60 appear to be protective, these findings suggest that circulating Hsp60 may be involved in the regulation of tolerance to self and immunity to bacterial forms of these widely expressed and structurally conserved proteins.